Analisis Hubungan Kemandirian Belajar, Kreativitas, dan Literasi Sains Siswa SMA di Pulau Taliabu Menggunakan Structural Equation Modeling-PLS - Ikhlashul Ihsan; Eva Vianti; Mujais Apling; Faradina; Fitri Ayu Lestari; Zulkifli I. Tuara (Academy of Social Science and Global Citizenship Journal, 2026)
The relationships among self-regulated learning, creativity, and scientific literacy among senior high school students on Taliabu Island were examined in this study using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. A quantitative correlational research design was employed, involving 104 respondents. Data were analyzed using SmartPLS through the evaluation of both the outer and inner models. The findings revealed that all variables were classified within moderate to high categories. However, no significant relationships were found between self-regulated learning and scientific literacy (β = 0.009; p = 0.927), creativity and scientific literacy (β = 0.023; p = 0.814), or self-regulated learning and creativity (β = −0.101; p = 0.307). An R-square value of 0.018 was obtained, indicating a very low predictive capability of the proposed model. The predominance of external factors in shaping scientific literacy in island regions was suggested by these findings.